Tin Oxide's Electronic Properties: Theoretical Insights on Band Structure and Mobility - Musawi, Ali Majeed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
This article presents a comprehensive theoretical study of the electronic properties of tin oxide (SnO2), with a particular focus on its band structure and carrier mobility. Through the utilization of density functional theory (DFT) and advanced computational methods, we delve into the intricacies of the electronic behavior of SnO2 . By solving the Schrödinger equation and the Kohn-Sham equation, we calculate the electronic energy eigenvalues and wave functions, which provide valuable insights into the band structure, effective mass, and carrier mobility of SnO2. Our findings contribute to a solid theoretical foundation for further experimental investigations and technological advancements in this field. In this study, we analyze the calculated band structure of SnO2 to determine the dispersion relationship between energy and wave vector in the Brillouin zone, shedding light on the nature of the bandgap, whether it is direct or indirect. Additionally, we investigate the valence band maxima and conduction band minima, crucial for understanding the transport of electrons and holes in SnO2. The results of our theoretical investigation reveal that SnO2 exhibits a well-defined bandgap, indicating its potential for effective control of electron and hole flow, thus making it suitable for diverse electronic applications. Moreover, the low effective masses of charge carriers in SnO2 facilitate their mobility, contributing to efficient charge transport within the material and enabling the development of high-performance electronic devices. By expanding our understanding of SnO2 electronic properties through theoretical investigations, we establish a solid foundation for further experimental studies and technological advancements in the field. The favorable electronic behavior of tin oxide paves the way for the development of advanced electronic devices, including optoelectronics, sensors, and energy devices, harnessing the unique characteristics of SnO2.